2013
DOI: 10.1080/09658211.2013.809765
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brain abnormalities and memory and learning outcomes at 7 years in children born very preterm

Abstract: Using prospective longitudinal data from 198 very preterm and 70 full term children, this study characterised the memory and learning abilities of very preterm children at 7 years of age in both verbal and visual domains. The relationship between the extent of brain abnormalities on neonatal magnetic resonance imaging (MRI) and memory and learning outcomes at 7 years of age in very preterm children was also investigated. Neonatal MRI scans were qualitatively assessed for global, white-matter, cortical grey-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 59 publications
5
91
2
Order By: Relevance
“…The scoring system on which this study was based has been used in 2 studies examining the relationships between TEA MR imaging and cognitive outcomes at 7 years. 24,25 Our results support previous findings at TEA and suggest that the brain changes associated with adverse cognitive outcomes are already present as early as 29 to 35 weeks PMA. 7 Of all MR imaging subscale scores, at early and term MR imaging, DGM demonstrated the strongest relationship with outcome.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The scoring system on which this study was based has been used in 2 studies examining the relationships between TEA MR imaging and cognitive outcomes at 7 years. 24,25 Our results support previous findings at TEA and suggest that the brain changes associated with adverse cognitive outcomes are already present as early as 29 to 35 weeks PMA. 7 Of all MR imaging subscale scores, at early and term MR imaging, DGM demonstrated the strongest relationship with outcome.…”
Section: Discussionsupporting
confidence: 82%
“…22 At TEA, global brain abnormality scores were significantly associated with motor outcomes at 2-years CA 23 ; and cognitive outcomes, at 7 years. 24,25 Deep gray matter scores were significantly associated with poorer attention and processing speeds, memory, and learning. 24,25 With safe earlier MR imaging now possible with MR compatible incubators, valid scoring systems for use earlier than TEA are required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very preterm (VPT; ,32 weeks' gestation) children are at increased risk for a range of neuropsychological deficits, including impairments in general intellect, 1 language, 2 visuoperceptual reasoning, 3 learning and memory, 4,5 attention, 6 and executive functioning. 7 Furthermore, neuroimaging studies of preterm infants and children have reported volumetric reductions in gray and white matter tissue, 8 as well as specific brain regions (cerebellum, basal ganglia, amygdala, hippocampi, and corpus callosum).…”
mentioning
confidence: 99%
“…Preterms also show a higher incidence of neurodevelopmental problems. For example, Omizzolo et al (2014) assessed 'very preterms' at 7 years of age for global, white-matter, cortical grey-matter, deep-grey-matter, and cerebellar abnormalities. They found brain abnormality in the 'very preterms' (<32 weeks) especially with the deep grey-matter and were able to associate these changes with poorer memory and learning performance (immediate memory, working memory, and long-term memory) as compared to full-term Controls.…”
Section: Contingency Learning In Pretermsmentioning
confidence: 99%